The gadget generation: BMI, physical activity & screen viewing durations of pre-school children in Kuantan, Pahang - Mohd Shukri, Nor Azwani; A. Ramos, Al-Hafizah; Ghazali, Jamilah; Sohaimi, Norhamizah; Abdul Basir, Siti Munirah (2016)
According to recent figures by WHO, the prevalence of overweight or obese children under five (almost 50% of whom live in Asia) increased by >30% since 1990. Sedentary lifestyle especially due to physical inactivity and increased screen viewing (SV) duration is identified as one of the risk factors of childhood obesity. This study aimed to investigate body mass index (BMI), SV and physical activity (PA) duration of pre-school children in Kuantan, Pahang. Information regarding duration of SV and PA was collected via a self-administered questionnaire, completed by the parents of 4-6 years old children attending 11 KEMAS kindergartens (categorized according to urban or rural areas). Height and weight of subjects were measured using a SECA stadiometer. This study included 284 subjects. The mean (±SD) of BMI was 15.1±2.5 kg/m2. Overall, 58.5% subjects have normal BMI, 25.3% were underweight and 16.2% were overweight/obese. A total of 87% of subjects reported to be using gadgets. In addition, 96% of the subjects reported >2 hours/day of total SV (which included television viewing & gadgets usage) duration, exceeding the international recommendation of <2 hours/day of screen time and Malaysian Dietary Guideline’s recommendation of <2 hours/day of sedentary activity. A total of 67% of the subjects met the recommended 1 hour/day of moderate PA. There were no significant differences of BMI, SV and PA durations between urban and rural areas. Preschoolers in Kuantan are largely found to have higher than recommended SV duration and only two thirds meet the recommended PA duration, regardless of urban or rural locations. This suggests that, the trend of sedentary lifestyle (particularly spending a lot time watching television and using tech devices) which may contribute to obesity among this Gadget Generation, is found to be prevalent across different geographical areas in this state capital of Pahang.